2020
DOI: 10.1186/s12889-020-09582-9
|View full text |Cite
|
Sign up to set email alerts
|

Health status of female Moldovan migrants to Italy by health literacy level and age group: a descriptive study

Abstract: Background Migration flows from Eastern Europe to Italy have been large and continue to grow. The purpose of this study was to examine the health status of a population of Moldovan migrant women, and their access to health care services in northern Italy, by age group and health literacy level. Methods We administered an ad-hoc questionnaire to adult Moldovan women. A bivariate analysis was conducted to test the association between health literacy and age groups with other variables (lifestyles, symptoms and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Notably, migrant workers living in unfamiliar places are affected by a variety of factors and their level of health literacy may not be comparable to that of the general population living in their country. The limited evidence generally reports that migrant workers have relatively low levels of health literacy [29,30]. This is consistent with the results of this study.…”
Section: Low Health Literacysupporting
confidence: 92%
“…Notably, migrant workers living in unfamiliar places are affected by a variety of factors and their level of health literacy may not be comparable to that of the general population living in their country. The limited evidence generally reports that migrant workers have relatively low levels of health literacy [29,30]. This is consistent with the results of this study.…”
Section: Low Health Literacysupporting
confidence: 92%
“…Migrant workers often lack access to health-related information, therefore exhibiting poor health literacy, which results in their poor healthcare [ 12 ]. This may be attributed to language barriers, cultural differences and limited knowledge of their rights, as seen in Sweden [ 13 ], Thailand [ 14 ] and Italy [ 15 ]. Therefore, migrant workers are particularly vulnerable to DF, and may risk transmitting DF to others.…”
Section: Introductionmentioning
confidence: 99%
“…While some of the workplace risks migrants face stem from being crowded into precarious forms of employment that are associated with high risks of workplace injury, international studies suggest that they also face particular occupational risks as migrants: 'social exclusion, lack of health and safety training, fear of reprisals for demanding better working conditions, linguistic and cultural barriers that minimise the effectiveness of training, incomplete OHS surveillance of foreign workers and difficulty accessing care and compensation when injured' (Benach et al, 2010, p. 1). Some recent studies have shown that migrants' home care work is especially hazardous, both physically and mentally (Ahonen et al 2010;Straiton et al 2017;Malhotra et al 2013;Smith 2011;Taylor, Donnelly 2006;Vianello et al 2020).…”
mentioning
confidence: 99%